A novel Arabidopsis phyllosphere resident Protomyces species and a re-examination of genus Protomyces based on genome sequence data - Kai Wang; Timo Sipilä; Kirk Overmyer (IMA Fungus)
Abstract Protomyces is an understudied genus of yeast-like fungi currently defined as phytopathogens of only Umbelliferae and Compositae. Species relationships and boundaries remain controversial and molecular data are lacking. Of the 82 named Protomyces, we found few recent studies and six available cultures. We previously isolated Protomyces strains from wild Arabidopsis thaliana, a member of Brassicaceae, a family distant from accepted Protomyces hosts. We previously sequenced the genomes of all available Protomyces species, and P. arabidopsidicola sp. nov. strain C29, from Arabidopsis. Phylogenomics suggests this new species occupied a unique position in the genus. Genomic, morphological, and physiological characteristics distinguished P. arabidopsidicola sp. nov. from other Protomyces. Nuclear gene phylogenetic marker analysis suggests actin1 gene DNA sequences could be used with nuclear ribosomal DNA internal transcribed spacer sequences for rapid identification of Protomyces species. Previous studies demonstrated P. arabidopsidicola sp. nov. could persist on the Arabidopsis phyllosphere and Protomyces sequences were discovered on Arabidopsis at multiple sites in different countries. We conclude that the strain C29 represents a novel Protomyces species and propose the name of P. arabidopsidicola sp. nov. Consequently, we propose that Protomyces is not strictly associated only with the previously recognized host plants.